Mahatma Gandhi : march to independence - Miller, Derek L. (New York Cavendish Square Publishing, 2018)
Mahatma Gandhi's commitment to peace and nonviolent resistance helped to secure India's independence, and came at a great personal cost. Gandhi's writings and protests, including the famed 1930 Salt March, have served as a blueprint for activists who recognize the power of peaceful protest. This book reveals Gandhi's story and includes historical information about Gandhi's effect on India and South Africa.
Who was Mahatma Gandhi? -- British India and South African apartheid -- Nonviolent resistance -- Gandhi's legacy.
Includes bibliographical references and index.
14 - 17 years
105820
Keywords: Gandhi -- Mahatma -- 1869-1948 -- Juvenile literature; Statesmen -- India -- Biography -- Juvenile literature; Nationalists -- India -- Biography -- Juvenile literature; Lawyers -- India -- Biography -- Juvenile literature; India -- Politics and government -- 1919-1947 -- Juvenile literature; South Africa -- Politics and government -- 1836-1909 -- Juvenile literature; Biography; Juvenile works